Mutagenesis Associated with DNA-Damage-Stress Response (Journal of Analytical Oncology, 2016)
In this manuscript we aim to take on the controversies in oncology, such as those related to costs and screening guidelines. Are we recently at new turning point with our existing methodology? During the past 30 years of evolution methods of awareness and screening have lead to an emphasis on early diagnoses of cancer and not only cancer. Recent trends and clinical trials show that these goals have not been met. International data demonstrate significant increase in early stage disease, without a proportional decrease in later-stage disease. We need to more differentiate in methodology because cancers are heterogenous with multiple paths, not all of which progress to metastases and death. This broader definition of disease named cancer must include also indolent disease that causes no harm during patients lifetime. Overdiagnosis and overtreatment result in billions of USD of wasted money. Our methodology must be completed with methods which take proper account of the real-life environment.